A heterogenic membrane-based biomimetic hybrid nanoplatform for combining radiotherapy and immunotherapy against breast cancer. (October 2022) - Pan, Pei; Dong, Xue; Chen, Ying; Ye, Jing-Jie; Sun, Yun-Xia; Zhang, Xian-Zheng
Abstract: Radiotherapy is adopted to obliterate multiple malignant tumors clinically, which might also induce antitumor immune response. However, traditional radiotherapy is not enough to ablate tumors and activate long-term immunological response. Here, we developed a hybrid nanoplatform (MGTe) composed of GTe (glutathione (GSH) decorated Te nanoparticles) and fusing tumor cell membranes (TM) and bacterial outer membranes (BM). In this nanoplatform, GTe was designed for radiotherapy sensitization, concurrently the fusion of TM and BM was expected for amplifying antitumor immune. With a high-Z element, MGTe could enhance radiosensitivity by reactive oxygen species (ROS) production and cancer cell immunogenic death (ICD) under X-ray irradiation, which would also trigger antitumor immune. At meanwhile, TM and BM would further enlarge the immunological effects through antigen presenting cells (APCs) maturation and cytotoxic T lymphocytes (CTLs) stimulation. In this synergistic strategy, the combination of MGTe and X-ray showed significant tumor inhibition by radiation-driven immunotherapy, which will find great potential as an attractive clinical alternative to fight against tumor with reduced side effects.